Neighborhood deprivation and obesity: Sex-specific effects of cross-sectional, cumulative and residential trajectory indicators. (August 2022) - Letarte, Laurence; Samadoulougou, Sekou; McKay, Rachel; Quesnel-Vallée, Amélie; Waygood, E.O.D.; Lebel, Alexandre; ,
Abstract: Obesity is a long-term health issue that is becoming increasingly prevalent. Very few studies have considered the life course effects of neighborhood characteristics on obesity. In a sample of 35, 856 adult participants (representative of the population of the Province of Quebec in Canada), we measured the association between neighborhood deprivation and obesity using logistic modelling on indicators of cross-sectional neighborhood deprivation, cumulative neighborhood deprivation and trajectories of neighborhood deprivation. For cross-sectional exposure, we found that females in our sample had higher odds of being affected by obesity when living in high-deprivation (OR 1.73, CI 1.41–2.13) or medium-deprivation neighborhoods (OR 1.27, CI 1.07–1.51) compared to females living in low-deprivation neighborhoods. Males also had higher odds of being affected by obesity when living in medium or high deprivation. For cumulative exposure to neighborhood deprivation, only females in the second highest category for longitudinal exposure to deprived neighborhoods had significantly higher odds of living with obesity (OR 1.89 CI 1.12–3.19) compared to females in the low cumulative exposure category. Using sequence analysis to determine neighborhood deprivation trajectories for up to 17 years, we found that females with a Deprived upward (OR 1.75 CI 1.10–2.78), an Average downward (OR 1.75 CI 1.08–2.84) or a Deprived trajectory (OR 1.81 CI 1.45–2.86) had higher odds of living with obesity compared to the Privileged trajectory. For males, there were no significant associations. Using trajectory indicators was beneficial to our analyses because this method shows that not only are individuals in low socioeconomic status neighborhoods at the end of their trajectory more susceptible to living with obesity, but so are those exposed to neighborhood deprivation at the beginning of their trajectory. These results could help to more precisely identify individuals at higher risk of developing obesity-related health issues. Highlights: Lifecourse theory suggests an effect of longitudinal exposure on health outcomes. Sequence analysis is useful to create lifecourse neighborhood deprivation trajectories. For females, high neighborhood deprivation trajectories are associated with obesity. For males, no neighborhood deprivation trajectory is associated with obesity.